Recommendations in covid-19 times: a view for home care - Luana Tonin; Maria Ribeiro Lacerda; Nayla Tamara de Godoi Caceres; Ana Paula Hermann (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To suggest recommendations for the practice of Home Nursing in the context of COVID-19. Method: Reflective study, originated from readings associated with the theme, available in current guidelines from the Pan American Health Organization, World Health Organization and the Ministry of Health. Results: Recommendations were developed from current scientific evidence for prevention of infections, control of epidemics and pandemics in the Brazilian home scenario. Final considerations: the reflections achieved contribute to guiding actions for better assistance to the patient, family caregivers and the community in the perspective of safe home care with COVID-19, and it is characterized as an introductory discussion on the theme, encouraging new studies to be carried out from the unfolding of the current scenario.